2011
DOI: 10.1093/humrep/der394
|View full text |Cite
|
Sign up to set email alerts
|

First trimester serum angiogenic/anti-angiogenic status in twin pregnancies: relationship with assisted reproduction technology

Abstract: In the first trimester, twin pregnancies conceived using ART showed a heightened anti-angiogenic status that could explain the increased risk of PE in these cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 45 publications
4
32
1
1
Order By: Relevance
“…We found that the PAPP-A and PlGF MoM levels were higher in women with a twin pregnancy than in those with a singleton pregnancy. These findings are consistent with those of previous studies [3637]. It has been reported that PlGF levels are lower in women with twin pregnancies who have PE, and the PAPP-A levels increase by the same magnitude that the PlGF levels reduce, which is considered to result from placental over-compensation [3738].…”
Section: Discussionsupporting
confidence: 92%
“…We found that the PAPP-A and PlGF MoM levels were higher in women with a twin pregnancy than in those with a singleton pregnancy. These findings are consistent with those of previous studies [3637]. It has been reported that PlGF levels are lower in women with twin pregnancies who have PE, and the PAPP-A levels increase by the same magnitude that the PlGF levels reduce, which is considered to result from placental over-compensation [3738].…”
Section: Discussionsupporting
confidence: 92%
“…Although the placenta is central to the process, it remains unclear; however, what causes sFlt-1 to increase and PlGF to decrease in women with preeclampsia or multiple gestation. 26 This study and others 27,28 demonstrate that women with twins can have much higher sFlt-1/PlGF levels (compared to singletons) and not develop preeclampsia. It is unclear why but it probably points to the multifactorial aspect of this disease.…”
Section: Commentsupporting
confidence: 54%
“…19,23 While we showed findings for maternal s-endoglin similar to those for sFlt-1 at the end of pregnancy, another study found no differences in the first trimester. 20 The etiology of the increases in sFlt1 has been hypothesized to be related to increased placental mass in twins as the placenta is thought to be the major source of sFlt. 24 Although the placenta is also the major source of PlGF, dramatic changes in PlGF are not seen with increased placental mass as the commercial assays to measure PlGF only measure the unbound form or free PlGF.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Another group has reported PlGF levels to be 59% higher in 61 dichorionic twins compared to 50 singletons when measured around 12 weeks on a different assay, and although they measure PlGF levels in 12 monochorionic pregnancies, they excluded these from analysis. Different commercial assays may detect the isoforms of PlGF differently, dependent upon the antibody pairs used.…”
Section: Discussionmentioning
confidence: 99%